MYT1 role in the microtia‐craniofacial microsomia spectrum. Issue 10 (1st September 2020) - Luquetti, Daniela V.; Heike, Carrie L.; Zarante, Ignacio; Timms, Andrew E.; Gustafson, Jonas; Pachajoa, Harry; Porras‐Hurtado, Gloria L.; Ayala‐Ramirez, Paola; Duenas‐Roque, Milagros M.; Jimenez, Natalia; Ibanez, Lina M.; Hurtado‐Villa, Paula
Abstract: Background: Craniofacial microsomia (CFM), also known as the oculo‐auriculo‐vertebral spectrum, comprises a variable phenotype with the most common features including microtia and mandibular hypoplasia on one or both sides, in addition to lateral oral clefts, epibulbar dermoids, cardiac, vertebral, and renal abnormalities. The etiology of CFM is largely unknown. The MYT1 gene has been reported as a candidate based in mutations found in three unrelated individuals. Additional patients with mutations in this gene are required to establish its causality. We present two individuals with CFM that have rare variants in MYT1 contributing to better understand the genotype and phenotype associated with mutations in this gene. Methods/Results: We conducted genetic analysis using whole‐exome and ‐genome sequencing in 128 trios with CFM. Two novel MYT1 mutations were identified in two participants. Sanger sequencing was used to confirm these mutations. Conclusion: We identified two additional individuals with CFM who carry rare variants in MYT1, further supporting the presumptive role of this gene in the CFM spectrum. Abstract : We conducted genetic analysis using whole‐exome and ‐genome sequencing in 128 trios with CFM. Two novel MYT1 mutations were identified in two participants, further supporting the presumptive role of this gene in the CFM spectrum.